PLACEMENT OF PRODUCTS ON CHINESE E-COMMERCE PLATFORMS: OPPORTUNITIES, CHALLENGES, AND STRATEGIC APPROACHES - SHARKO, Vitalii; HAVENKO, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This paper explores the opportunities, challenges, and strategic approaches for Ukrainian enterprises entering Chinese e-commerce platforms, one of the largest and fastest-growing digital markets in the world. The study emphasizes the critical role of e-commerce in international trade, highlighting China’s dominance in global online retail with platforms such as Tmall, JD.com, Pinduoduo, Douyin, and Xiaohongshu. Special attention is given to the placement of Ukrainian agricultural and organic products, which are gaining traction among Chinese consumers due to rising demand for certified high-quality and eco-friendly goods. The paper analyzes trade performance indicators, identifies key barriers such as language, cultural differences, logistics, and regulatory compliance, and discusses the adaptation strategies required for successful market entry. Case studies of exporters are summarized to illustrate practical approaches to overcoming obstacles, including localization of branding and packaging, partnerships with Chinese logistics operators, and the use of cross-border e-commerce models. Furthermore, the research underlines the significance of digital marketing tools—such as influencer marketing, livestream sales, and social commerce integration—as essential drivers of visibility and competitiveness on Chinese platforms. The paper argues that a comprehensive strategy, combining segmentation of target audiences, localization, regulatory alignment, and strategic alliances with local distributors or Tmall Partners, is crucial for sustainable growth in the Chinese market. Ultimately, product placement on Chinese e-commerce platforms is not only a commercial opportunity but also a pathway to deeper integration into the global digital economy, enhancing brand recognition, diversifying distribution channels, and expanding the long-term export potential of Ukrainian enterprises.
Keywords: e-commerce; affiliate marketing; China; e-commerce platforms; organic products; agricultural export; logistics; joint programs; distribution